EXPLORING HERITAGE: SOCIOLINGUISTICS ANALYSIS ON SLANG WORD IN AFRICAN AMERICAN ENGLISH (AAE) IN TIKTOK’S COMMENTS - Fifih Latifah; Hendar (Lembaga Penelitian Universitas Pasundan, 2024)
This study examines language issues that arise in social media. Users of TikTok frequently contribute images, videos, and memes. Users of TikTok also left comments on the post in a variety of languages. Slang is used, and the language style has been studied. The purpose of this study was to understand how slang is put together, what it means, and what its function is. The justification for utilizing slang was revealed in user comments on TikTok. The researcher is interested in talking about the phenomena of African American English slang terms seen in comments on TikTok social media with regard to this issue. Additionally, this study uses a qualitative, descriptive approach. The information was gathered from TikTok users' comment sections over a specific time period. The theory of the functions of slang is from Zhou and Fan (2013), and the framework for the types of slang is based on the theory of Allan & Burridge (2006). The analysis's findings indicate that there are four categories of slang utilized by TikTok users: Clipping, Acronyms, Fresh and Creative, and Flippant. Slang among TikTok users serves purposes related to pursuing self-identity and emotive feelings. The sociolinguistic approach is utilized to better comprehend the slang expressions found in TikTok comments and to address the two issues that have resulted from them.